17‐2: Integrated Self‐Capacitance Touch Panel for Flexible OLED Display. Issue 1 (28th June 2022) - Lu, Feng; Li, Zhe; Zhou, Zihan; Zhang, Jing; Yao, Qijun; Ding, Yuan; Lu, Yung-Sheng; Chuang, Jui-Chuan; Chen, Chien-Chuan
Abstract : Designs of self‐capacitance "on‐cell" touch panel were implemented in a 6.2inch foldable OLED panel with singlelayered sensor pattern. The test results showed that the self‐capacitance "on‐cell" touch panel has high sensitivity even with TFTs connected in serial of the sensor channels. Weaker retransmission effect was also found compared with its mutual‐capacitance counterpart. The self‐capacitance touch panel has shown great potential of application in future OLED display products.